Does copper deficiency predispose children to otitis media with effusion? - Amizadeh, Maryam; Molaei Moghbeli, Sareh; Reihani-Kermani, Hamed; Reihani, Amir (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Both otitis media with effusion (OME) and copper or selenium have been associated to the immune system, hence it could be proposed that cooper and/or selenium deficiency predisposes children to OME through immune cells dysfunction. The aim of this study was to determine the serum levels of Copper and Selenium in an immundeficient-linked disease - OME – in childhood. Methods: This cross-sectional study was conducted between July 2015 and December 2016 including 80 patients age 1 to 8 years old who were divided into two groups: otitis media with effusion (OME) consisted of 40 patients and the control (n=40). Patients who did not recover after three months conservative treatments were included. Serum levels of Copper and Selenium were measured using graphite furnace atomic absorption spectrometry. Results: Statistical analysis showed no significant differences regarding age and sex were noted between groups. Patients with OME had significantly lower serum copper levels than the control group (p=0.007). However, there was no statistically significant difference in serum selenium levels between groups. The analysis also showed a significant positive correlation between serum copper level and age (correlation coefficient=0.348, p=0.028), whereas, there was no correlation between the measured selenium level and age. Conclusions: The results of the present study showed that serum level of copper might play a role on development of otitis media with effusion in childhood.